1996
DOI: 10.1007/s004030050068
|View full text |Cite
|
Sign up to set email alerts
|

Role of fibroblasts in the regulation of proinflammatory interleukin IL-1, IL-6 and IL-8 levels induced by keratinocyte-derived IL-1

Abstract: In the epidermis, the keratinocytes are the first cells to be encountered by external stimuli and they are able to promote the inflammatory response by increased production and release of various cytokines. In their turn, these cytokines may directly affect the production of proinflammatory cytokines in human dermal fibroblasts. In addition, in both epithelial and mesenchymal cells cytokine production may be modu lated by their mutual interaction, and thereby regulate the inflammatory response. The present stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

1999
1999
2007
2007

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 11 publications
1
4
0
Order By: Relevance
“…The 2 cytokines could be detected in control skin organ cultures, and levels of both were increased in the presence of the two contactsensitizers examined. These data are consistent with previous findings from epidermal-equivalent or skin-equivalent cultures (Ponec and Kempenaar, 1995;Boxman et al, 1996; 700 VARANI ET AL.…”
Section: Discussionsupporting
confidence: 92%
“…The 2 cytokines could be detected in control skin organ cultures, and levels of both were increased in the presence of the two contactsensitizers examined. These data are consistent with previous findings from epidermal-equivalent or skin-equivalent cultures (Ponec and Kempenaar, 1995;Boxman et al, 1996; 700 VARANI ET AL.…”
Section: Discussionsupporting
confidence: 92%
“…Those fibroblasts that participate in wound repair would be expected to respond to this factor. IL-6 is an inflammatory cytokine that is produced by many different types of cells in skin, including dermal fibroblasts (Boxman et al 1993(Boxman et al , 1996. This factor regulates the differentiation of monocytes and plays a role in the communication of fibroblasts with epidermal cells; these events may include the regulation of epidermal cell proliferation and migration, both of which are features important for wound repair (Turksen et al 1992;Waelti et al 1992;Boxman et al 1993;Chomarat et al 2000;Gallucci et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Generally, cytokines other than IL-6 play a role in the regulatory secretion of IL-6 through their interaction with keratinocytes, T cells, and the extracellular matrix. Autocrine regulation of IL-6 is affected by IL-6 itself and other pro-inflammatory factors (Maruyama et al, 1995;Boxman et al, 1996;Sporri et al, 1996). Some studies have shown that interferon (IFN)-g regulates IL-6 secretion from fibroblasts by stimulating the expression of MHC class II and CD40 (Mourad et al, 1992;Yellin et al, 1995).…”
Section: Discussionmentioning
confidence: 99%